Real-World Treatment Patterns according to Clinical Practice Guidelines in Patients with Type 2 Diabetes Mellitus and Established Cardiovascular Disease in Korea: Multicenter, Retrospective, Observational Study - Ye Seul Yang; Nam Hoon Kim; Jong Ha Baek; Seung-Hyun Ko; Jang Won Son; Seung-Hwan Lee; Sang Youl Rhee; Soo-Kyung Kim; Tae Seo Sohn; Ji Eun Jun; In-Kyung Jeong; Chong Hwa Kim; et al. (Diabetes & Metabolism Journal, 2024)
Background Recent diabetes management guidelines recommend that sodium-glucose cotransporter 2 inhibitors (SGLT2is) or glucagon-like peptide 1 receptor agonists (GLP-1RAs) with proven cardiovascular benefits should be prioritized for combination therapy in patients with type 2 diabetes mellitus (T2DM) and established cardiovascular disease (CVD). This study was aimed at evaluating SGLT2i or GLP-1RA usage rates and various related factors in patients with T2DM and established CVD. Methods We enrolled adults with T2DM aged ≥30 years who were hospitalized due to established CVD from January 2019 to May 2020 at 13 secondary and tertiary hospitals in Korea in this retrospective observational study. Results Overall, 2,050 patients were eligible for analysis among 2,107 enrolled patients. The mean patient age, diabetes duration, and glycosylated hemoglobin level were 70.0 years, 12.0 years, and 7.5%, respectively. During the mean follow-up duration of 9.7 months, 25.7% of the patients were prescribed SGLT2is after CVD events. However, only 1.8% were prescribed GLP-1RAs. Compared with SGLT2i non-users, SGLT2i users were more frequently male and obese. Furthermore, they had a shorter diabetes duration but showed worse glycemic control and better renal function at the time of the event. GLP-1RA users had a longer duration of diabetes and worse glycemic control at the time of the event than GLP-1RA non-users. Conclusion The SGLT2i or GLP-1RA prescription rates were suboptimal in patients with T2DM and established CVD. Sex, body mass index, diabetes duration, glycemic control, and renal function were associated with the use of these agents.